Gambaran Performa Instruktur Clinical Skill lab pada Masa Pandemi Covid-19 di Fakultas Kedokteran UMI - Putri, Adinda Pradana; Arifin, Arina Fathiyyah; Rijal, Syamsu; Irwan, Andi Alamanda; Arfah, Arni Isnaini (Rumah Sakit Ibnu Sina, Makassar, 2024)
Skill labs are an important means for students to practice clinical skills, prepare them to achieve competency standards during their undergraduate education, and prepare themselves before entering professional education. Skill lab involves practicing communication skills, physical examination, as well as medical actions and invasive procedures. This study aims to determine the performance of clinical Skill lab instructors during the Covid-19 pandemic at the Faculty of Medicine, Universitas Muslim Indonesia (UMI), Class of 2019. Using a cross-sectional design, all respondents filled out a questionnaire through the Google Form application. Of the 155 respondents, 96.1% rated the instructor's teaching skills as good and very good, 92.9% rated the instructor's interpersonal and communication skills as good, and 92.9% rated the clinical skills training conditions or strategies at FK UMI as good. In general, the performance of clinical Skill lab instructors during the Covid-19 pandemic at FK UMI Class of 2019 is considered good based on student perceptions.